Women's Struggle against Patriarchy: An Analysis of Radical Feminism Through Nadia Hashimi's A House Without Windows - Naily Syiva Fauzia; Anik Cahyaning Rahayu (Anaphora : Journal of Language, Literary, and Cultural Studies, 2019)
Under twenty years of war, women in Afghanistan suffer from oppressive situations and rules resulting in inequality and injustice. Afghanistan women face difficulties at all levels of Afghanistan patriarchal society. Male domination is the root cause of damaging to women’s rights in Afghanistan that brings impact to inferiority of Afghanistan women. Using radical feminism by Kate Millet, this paper tries to describe the struggle of Afghanistan women in gaining opportunities to move forward in their society. The analysis is focused on the female characters who deal with problem solving to their unfair condition such as Zeba, Gulnaz, Latifa, , Mezghan, Bibi Shireen, the wife of judge Najeeb, Sitara, Meena, and Aneesa. They begin to build self-consciousness, to demand autonomy in decision making, to declare resistance to be controlled by the men, and to get their basic rights such as the right to speak, the right to get education, and the right to work to earn money. The strong self-awareness and determination as reflected from the female characters are the women’s primary step to get rid of male domination and to proceed in their lives as well as in their society. Through this literary evidence, radical feminism emphasizes that women’s efforts to protect their rights means approval that inequality and lack of opportunities for women still happen